Revisiting the category of care.: An ethical analysis of the hospice care - Radosta, Darío Iván (2021)
The purpose of this work is to analyze the category of care as an ethical value. For this I propose to retake an approach called ethics of care, exposing its main characteristics. I consider that one of the main criticisms made to this theory has to do with the indeterminacy of the normative content of the notion of care, and the subsequent impossibility of formulating a complete ethical theory that uses it as a fundamental category in directing the moral action of people. To circumvent this limitation, I have sought to analyze the category of care based on the specific context in which it is carried out. For this I have taken, as empirical material, the philosophy of hospice care, used in the care of people with terminal illnesses at the end of life within the institutions belonging to the modern hospice movement. Arguing in what way this philosophy can be understood as an ethics of care, I will expose that its study provides tools to overcome some of the criticisms that have been commonly made to this approach, also showing the limitations that this specific type of care has when extrapolating it to a general ethical theory.